Pharmacogenetics: an illustration of personalized pharmacotherapy - Allegaert, Karel (Henry Stewart Talks, 2024)
Introduction to pharmacogenetics, Genetic polymorphisms, Polygenetic response, Pro-drugs, Adverse effects